2011
DOI: 10.1073/pnas.1014249108
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-inlet mass spectrometry reveals a high driving force for oxygen production by photosystem II

Abstract: Oxygenic photosynthesis is the basis for aerobic life on earth. The catalytic Mn 4 O x CaY Z center of photosystem II (PSII), after fourfold oxidation, extracts four electrons from two water molecules to yield dioxygen. This reaction cascade has appeared as a single four-electron transfer that occurs in typically 1 ms. Inevitable redox intermediates have so far escaped detection, probably because of very short lifetime. Previous attempts to stabilize intermediates by high O 2 -back pressure have revealed contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…They were always more efficient than the S 2 3 S 3 transition. This is not entirely surprising because recent studies have shown that O 2 release during the S 3 3 S 0 transition is not limited thermodynamically and highly exothermic, indicating that possibly this is not the most difficult transition in the S cycle (48,49).…”
Section: Significance Of Kok Parameters In Our Analysis: Involvement mentioning
confidence: 90%
“…They were always more efficient than the S 2 3 S 3 transition. This is not entirely surprising because recent studies have shown that O 2 release during the S 3 3 S 0 transition is not limited thermodynamically and highly exothermic, indicating that possibly this is not the most difficult transition in the S cycle (48,49).…”
Section: Significance Of Kok Parameters In Our Analysis: Involvement mentioning
confidence: 90%
“…The influence of elevated O 2 concentrations has been investigated previously (15,16). In time-resolved x-ray experiments, no inhibition of the O 2 evolution transition (S 3 3 S 0 ϩ O 2 ) was detected, up to pO 2 of 16 bar, suggesting that the Gibbs free energy of any reaction intermediate is Ͼ130 meV higher than for the product state (S 0 ϩ O 2 ) (16), as recently confirmed by mass spectroscopy (17) and for intact cells (18). (Here and in the following, we use, for simplicity, the term free energy or ⌬G instead of standard free energy or ⌬G 0 .)…”
mentioning
confidence: 90%
“…The presence of O 2 does not, however, inhibit O 2 production by oxygenic photosynthetic organisms [81,82]. The accumulation of O 2 in the habitats of oxygenic photosynthetic organisms using Rubisco as their autotrophic carboxylase permits Rubisco oxygenase activity to occur, provided the CO 2 concentration is below saturation for Rubisco.…”
Section: Oxygen Accumulation Rubisco Oxygenase and The Metabolism Ofmentioning
confidence: 99%